Unnatural amino acid incorporation in E. coli: current and future applications in the design of therapeutic proteins - Ovaa, Huib; wals, kim (Frontiers in Chemistry, 2014)
Unnatural amino acid (UAA) incorporation by amber codon suppression offers scientists a powerful tool to modify the properties of proteins at will. UAA incorporation has been used for a plethora of fundamental research applications and, more recently, also for the selective modification of therapeutic proteins. In this review most recent developments in Escherichia coli codon expansion and, unnatural amino acid incorporation are discussed together with some remarkable recent developments in improved efficient UAA incorporation. We focus on the generation of proteins that hold promise for future therapeutic applications that would be impossible to obtain without unnatural amino acid incorporation, including the generation of bi-specific antibodies and antibody drug conjugates.